FAKTOR –FAKTOR YANG MEMPENGARUHI KEBIJAKAN DIVIDEN PADA PERUSAHAAN SEKTOR NON KEUANGAN YANG TERDAFTAR DI BEI PERIODE 2012-2016 - Desi Teliana Silim; Werner Ria Murhadi; Endang Ernawati (Perpustakaan Universitas Surabaya, 2018)
This study aims to investigate the determinants of corporate dividend policy. Variabel used in this research is size, profitability, growth, cash, leverage, systematic risk (β) and investment opportunity. This Study uses the quantitative approach and multiple linear regression. The target populations of this study are all non-financial sector companies registered in Indonesia Stock Exchange in 2012-2016 which are equal to 1045 year observations. Subsequently, the robustness test is performed by clustering the target populations by company size, that is large company groups and small company groups. The study finds that size, profitability, cash and investment opportunity affect dividend policy negatively. While growth, leverage and systematic risk (β) affect dividend policy positively.